Education in languages of lesser power : Asia-Pacific perspectives - Volker, Craig Alan, 1953-; Anderson, Fred E. (Fred Einar) (Impact, studies in language and society, 2015)
Pasifika peoples in Aotearoa New Zealand are amongst the fastest growing population of all the minority groups. The 2006 census shows that the Pasifika population makes up 6.9% of the total New Zealand population (Statistics New Zealand 2009). The current projections are that this figure will increase in 2026 to 18%. Many of the children who are at present strong in their language are in danger of becoming either monolingual, speaking English only. Samoan children in bilingual classes can achieve equally or higher than their Samoan counterparts in mainstream classrooms. This paper argues that.